Pemanfaatan ERP Odoo sebagai Media Pembelajaran Teknis Multijurusan di SMK PGRI 3 Bogor - Amelia Oktrivina; Yetty Murni; Salis Musta ‘Ani; Shanti Lysandra; Sailendra Sailendra; Agung Terminanto; Amanda Putri Alisha; Putri Rizki Samsumantri (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance the competencies of students at SMK PGRI 3 Bogor in understanding integrated business processes through the use of Enterprise Resource Planning (ERP) Odoo as a cross-disciplinary technical learning medium. The program was designed to address the limited implementation of integrated system-based learning and to improve students' readiness for the demands of the business and industrial sectors. The implementation methods included socialization, training, hands-on ERP Odoo practice, mentoring, and evaluation using pre-test and post-test assessments. The program involved 28 eleventh- and twelfth-grade students from five vocational study programs: Accounting, Online Business and Marketing, Visual Communication Design, Office Management, and Logistics Management. The evaluation results showed that the average post-test score increased by more than 30% compared with the pre-test score. In addition, 85% of the participants were able to operate ERP Odoo modules according to their respective areas of expertise. The program also produced an ERP Odoo-based learning medium that can be sustainably utilized by the school to support cross-disciplinary learning. Overall, the program contributed to improving students' digital competencies, strengthening their understanding of integrated business processes, and supporting vocational learning that is better aligned with the needs of the business and industrial sectors.